Hubungan Riwayat Asma dan Riwayat Komorbiditas dengan Kejadian Pneuomonia pada Balita (Studi di Wilayah Kerja Puskesmas Bandaharjo Kota Semarang) - Widya Widya; Bagoes Widjanarko; Apoina Kartini; Dwi Sutiningsih; Suhartono Suhartono (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: The incidence of pneumonia in children under five in the working area of the Bandaharjo Community Health Center in 2017 was 443 cases, 2018 was 328 cases, 2019 was 485 cases and in 2020 to June was 231 cases. A history of asthma and a history of comorbidities (anemia and diarrhea) is thought to be one of the determining factors that can cause children under five to develop pneumonia. The purpose of this study was to analyze the history of asthma and comorbid history associated with the incidence of pneumonia in children under five in the Bandaharjo Community Health Center, Semarang City.Methods: This observational study used a case control design used in this study, with a sample of 80, namely 40 case samples and 40 control samples. The study population was all toddlers who seek treatment and live in the working area of Puskesmas Bandaharjo. The sample of cases in this study were toddlers who had pneumonia in January-June 2020, while the control sample was toddlers who did not have pneumonia 1 in January-June 2020. Data collection was through interviews. Data analysis used chi-square test and multiple logistic regression.Results: There was a relationship between history of asthma (p; 0.01; OR 19.5; 95% CI 6.23-61.15), history of comorbidities (p; 0.01; OR 22.91; 95% CI 5, 97-87,83) with the incidence of pneumonia in children under five.Conclusion: History of asthma and history of comorbidity have a strong relationship with the incidence of pneumonia in children under five in the working area of the Bandaharjo Community Health Center, Semarang City.